The academic book and its digital dilemmas - Spence, Paul (Convergence: The International Journal of Research into New Media Technologies, 2018)
The future of the academic book has been under debate for many years now, with academic institutional dynamics boosting output, while actual demand has moved in the opposite direction, leading to a reduced market which has felt like it is in crisis for some time. While journals have experienced widespread migration to digital, scholarly monographs in print form have been resilient and digital alternatives have faced significant problems of acceptance, particularly in the arts and humanities. Focusing in particular on the arts and humanities, this article asks how, and under what conditions, the digitally mediated long-form academic publication might hold a viable future. It examines digital disruption and innovation within humanities publishing, contrasts different models and outlines some of the key challenges facing scholarly publishing in the humanities. This article examines how non-traditional entities, such as digital humanities research projects, have performed digital publishing roles and reviews possible implications for scholarly book publishing’s relationship to the wider research process. It concludes by looking at how digital or hybrid long-form publications might become more firmly established within the scholarly publishing landscape.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzU0ODU2NTE4NzcyMDI5